KOMPETENSI LITERASI DIGITAL KEPALA SEKOLAH DI SD MUHAMMADIYAH RIMBO BUJANG DAN SD NEGERI 119/VIII KABUPATEN TEBO - Anjar Tri Pangesti; Dian Hidayati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Reinforcing activities, in terms of literacy, are programs or activities that aim to train school principals by leveraging digital literacy. In the development of competency improvement, digital literacy is a form of attempt that was applied at SD Negeri Tebo 119. Hence, the researchers are interested to examine the school principal’s digital literacy competency at SD Muhammadiyah Rimbo Bujang and SD Negeri 119/VIII Tebo. The method used was a qualitative method with a descriptive approach. The implementation of digital literacy competencies needs to be applied with repetitive steps in order to overcome the problems in the digital era. Digital literacy competencies are required in the academic aspects totally. Teachers at SD Muhammadiyah Rimbo Bujang and SD Negeri 119/VIII Tebo were less skilled in implementing Science and Technology and they could use every software in teaching activity, such as Microsoft Office, editing, and any educational applications. The need for development in a national literacy movement should be applied by the government through planning regarding digital literacy as one part of the six national literacies. Digital literacy is very important to be applied by school principals in order to control the available information in the media.